Implementasi Peran Pemerintah Daerah Kabupaten Lampung Selatan dalam Melestarikan Destinasi Pariwisata Perspektif Siyasah Tanfidziyyah - Tri Sukmawati; Erina Pane; Ahmad Burhanuddin (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the implementation of supervision and evaluation in the management of tourism destinations based on Article 11K of Law Number 18 of 2025 concerning Tourism, focusing on the culinary tourism area of Dermaga Bom in South Lampung Regency, from the perspective of siyāsah tanfīdziyyah. Academically, this research is significant due to the existing gap between legal norms emphasizing supervisory and evaluative functions and their empirical practice at the regional level. The policy gap examined lies in the absence of systematically formulated, measurable and sustainable operational mechanisms for supervision and evaluation as a derivative of Article 11K. This research employs a qualitative method with an empirical approach through in-depth interviews and field observations. The analysis is conducted using the indicators of siyāsah tanfīdziyyah, which include: (1) policy implementation (tanfīdz alahkām), (2) effectiveness of supervision (al-raqābah), (3) governmental accountability and (4) orientation toward public welfare (tahqīq al-maṣlaḥah). The findings reveal that the implementation of supervision and evaluation has not been optimal due to limited human resources, weak inter-agency coordination, and the absence of a structured and sustainable evaluation system. These conditions result in poorly organized spatial management, limited facilities, inadequate security assurance and low community participation. Legally, these findings indicate that the mandate of Article 11K of Law Number 18 of 2025 concerning Tourism has not been fully fulfilled in the practice of regional governance. The implications of this study highlight the need to strengthen derivative regulations, enhance the institutional capacity of regional governments, and develop participatory-based supervision and evaluation systems to achieve effective, accountable and public welfare-oriented tourism governance.